Augmented-reality-driven medical simulation platform for percutaneous nephrolithotomy with cybersecurity awareness. (April 2019) - Tai, Yonghang; Wei, Lei; Zhou, Hailing; Peng, Jun; Li, Qiong; Li, Feiyan; Zhang, Jun; Shi, Junsheng
With cybersecurity guaranteed, a novel augmented-reality-driven medical simulation platform was designed for percutaneous renal access, which can overcome the limitations of conventional bench simulators and existing augmented reality models. This article presents a new framework design and establishes validations for the simulator for percutaneous nephrolithotomy (SimPCNL) assessment with the consideration of cybersecurity in the implementation. In particular, the new cybersecurity awareness design includes code security and hardware security. SimPCNL is mainly composed of a personal computer and two PHANTOM Omni (three-dimensional haptic device) with one stylus that mimics the percutaneous needle. A database storing clinical fluoroscopic images of percutaneous nephrolithotomy and a reproduced visual–haptic environment mimicking actual surgical performance consist of the training interface. In total, 54 professors comprising 36 medical students and 18 urologists were employed to evaluate the simulator we designed, which performed in the surgical department of Yunnan First People's Hospital. Objective metrics and Global Rating Scale questionnaire are used to record the face and content validities, skills improvement validity, construct validity, and criterion validity. The median appraisal value of the face and content was 4 (1–5) by 18 urologists. Professors' results demonstrated extremely better than medical students' in total evaluation results. After a training group of medical students, SimPCNL showed a better result than the commercial training framework, especially for the quantitative feedbacks group. SimPCNL Global Rating Scale scores and objective assessment demonstrated a better result than PERC Mentor in percutaneous renal access surgical training. Training percutaneous renal access on SimPCNL is reliable and versatile through the face, content, improvement construct, and criterion validations. Furthermore, we also consider cybersecurity when implementing our novel platform.